2020
DOI: 10.1101/2020.07.24.211136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic Response of Brain Tissue to Focused Ultrasound-Mediated Blood-Brain Barrier Disruption Depends Strongly on Anesthesia

Abstract: Focused ultrasound (FUS) mediated blood brain barrier disruption (BBBD) is a promising strategy for the targeted delivery of systemically-administered therapeutics to the central nervous system (CNS). Pre-clinical investigations of BBBD have been performed on different anesthetic backgrounds; however, the potential influence of the choice of anesthetic on the molecular response to BBBD is unknown, despite its potential to critically affect interpretation of experimental therapeutic outcomes. Here, using bulk R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…This profile Previous studies have revealed that BBB opening by ultrasound is a reversible process and that it is fully restored after 24 h as measured by contrast-enhanced MRI. 23 Our previous studies have observed a reduction in Aβ plaque load following an ultrasound treatment paradigm consisting of five to seven treatments repeated on a weekly basis, 13 whereas other studies have observed a response in bulk tissue (including microglia) ranging from 1 week after 6 weekly treatments, 26 and 6 27,28 and 24 h 27,29,30 after a single treatment. As microglia are a cell population presenting with a fast and dynamic response depending on both the intensity and time-point after stimulation (acute vs. chronic response), we sought to observe the transcriptomic changes in these cells outside of the acute response of microglia to BBB opening.…”
Section: Discussionmentioning
confidence: 97%
“…This profile Previous studies have revealed that BBB opening by ultrasound is a reversible process and that it is fully restored after 24 h as measured by contrast-enhanced MRI. 23 Our previous studies have observed a reduction in Aβ plaque load following an ultrasound treatment paradigm consisting of five to seven treatments repeated on a weekly basis, 13 whereas other studies have observed a response in bulk tissue (including microglia) ranging from 1 week after 6 weekly treatments, 26 and 6 27,28 and 24 h 27,29,30 after a single treatment. As microglia are a cell population presenting with a fast and dynamic response depending on both the intensity and time-point after stimulation (acute vs. chronic response), we sought to observe the transcriptomic changes in these cells outside of the acute response of microglia to BBB opening.…”
Section: Discussionmentioning
confidence: 97%
“…Inspired by these observations, emerging investigations have demonstrated that MB-FUS can enhance the accumulation of immune adjuvants in the brain TME and improve survival in different murine brain tumor models, including GBM (26)(27)(28). Despite these encouraging findings and extended work on healthy brains and brain tumors, as well as other disease models (e.g., Alzheimer's) (25,(29)(30)(31)(32), the treatment window (i.e., FUS exposure) to elicit distinct immuno-mechano-biological effects and promote effective therapeutic trafficking in the brain TME remains poorly defined. This is because current studies in brain tumors typically report only the estimated focal pressure (26)(27)(28)32) and not the MB acoustic emissions generated during the sonication (29,33,34), which is critical for making accurate inferences about the strength and type (stable versus inertial) of the MB oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Focused ultrasound has been shown to trigger the endothelium to release nitric oxide resulting in dilation of blood vessels [21]. Activation of the endothelial cells by focused ultrasound treatment supports VEGF signaling, angiogenesis, and restoration of the BBB, most notable under the anesthetic isoflurane, which was used in the present study [22]. These changes may play a central mechanistic role in the neuroprotective properties of LIFU under ischemic stroke conditions.…”
Section: Discussionmentioning
confidence: 64%
“…Further studies are needed to test the therapeutic window, for example, application up to 6-8 hrs postonset of stroke, using large animal models to adjust for skull thickness, as well as uncovering the cellular and molecular mechanisms underlying neural tissue protection that may include microvascular remodeling. Additional modes of action may include modulation of BBB, edema, vasospasms, tissue permeability, interstitial flow, and innate immune regulation [22,[25][26][27]. Overall, this work demonstrates the neuroprotective properties of LIFU in a murine model of stroke and provides insight into its possible role as a novel neural therapeutic for the treatment of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 72%